No Gadget More Story, Gerakan Literasi Girimukti - Elok Yulia Widayanti; Cinta Wahyuning Suci; Stepanus Dedy Deomedes (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
The problem of low reading interest among elementary school students is further exacerbated by the high use of gadgets, which often distract students from literacy activities. This situation prompted the implementation of the